High Neutrophil to Lymphocyte Ratio Is Associated With Symptomatic and Ruptured Thoracic Aortic Aneurysm. (September 2018) - Lareyre, Fabien; Raffort, Juliette; Le, Duy; Chan, Hon Lai; Houerou, Thomas Le; Cochennec, Frédéric; Touma, Joseph; Desgranges, Pascal
The predictive value of the neutrophil to lymphocyte ratio (NLR) has been demonstrated in several cardiovascular diseases. The aim of our study was to investigate the association between the preoperative NLR and aneurysm characteristics as well as 30-day postoperative morbidity and mortality in patients with thoracic aortic aneurysm (TAA) undergoing aortic surgical repair. Consecutive patients (n = 75) with TAA were retrospectively included over a 10-year period. Clinical characteristics, aneurysm characteristics, and 30-day postoperative outcome were recorded. The median age of patients was 71 (67-80) years. The median preoperative NLR was 3.5 (2.3-5.8). The proportion of asymptomatic TAA was significantly lower in patients with an NLR > 3.5 compared with those with an NLR < 3.5 (52.6% vs 75.7%; P = .054). The proportion of patients with pain or with ruptured TAA was significantly higher in patients with an NLR > 3.5 compared with those with NLR < 3.5 (42.1% vs 16.2%; P = .022 and 26.3% vs 2.7%; P = .007, respectively). No significant difference was observed regarding the 30-day overall postoperative mortality and morbidity. The preoperative NLR did not correlate with TAA diameter. A high preoperative NLR is significantly associated with symptomatic and ruptured TAA, suggesting a potential interest as a marker and/or player in the disease.